Hard clam resilience to marine heatwaves in the face of climate change - Liang, Jian; Masanja, Fortunatus; Li, Yongren; Guo, Yongjun; Deng, Yuewen; Zhao, Liqiang (Frontiers in Marine Science, 2024)
The frequency and severity of marine heatwaves (MHWs) have reached new heights in the last two decades. Intensifying MHWs can affect intertidal bivalves, but the extent of their impacts remains largely underestimated. Here, we tested how persistent (P-MHW) and repeated (R-MHW) MHWs events affected the physiological energetics of ecologically and economically clams Mercenaria mercenaria inhabiting intertidal habitats. Compared to individuals maintained under ambient conditions, the clams exposed to both two scenarios of MHWs exhibited significant increases in their clearance rate, absorption efficiency, respiration rate, excretion rate, and scope for growth, showing compensatory energetic mechanisms to cope with MHWs. Especially, physiological energetics of M. mercenaria were more sensitive to repeated than persistent scenarios of MHWs. Given that the physiological response can act as an early and sensitive indicator of the fitness of intertidal bivalves, our results indicated that M. merceneria can likely hold the ability to readily recover from repeated to persistent exposure MHWs, enabling its continued resilience in a rapidly changing marine environment.